EFEKTIVITAS MODEL PEMBELAJARAN KONTEKSTUAL DAN PENERAPANNYA DALAM PEMBINAAN WARGA GEREJA - Pranada Pane (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2022)
The formation of Church members is a very important task and must be carried out by the church for its members. Likewise, the formation of church members is a form of the church's responsibility to the Lord Jesus Christ who is the head of the church and also to others who in its understanding are to the congregation. Coaching is carried out with the aim of exploring and developing all the potential within the congregation and ultimately being applied in the ministry and dedicated to the interests of the Kingdom of God. As for the background of this writing, the author finds a church that is unconscious and also without adequate provisions to carry out the formation of church members even though it must be realized that coaching is something that is necessary and must be done so that the needs of the congregation are met, especially in spirituality. the congregation. To get information about the formation of the congregation, the author uses questions that the author conveys to the church members to ensure that the congregation receives guidance or not and if the congregation receives guidance to what extent and how the implementation of the coaching is carried out, because if the church can carry out coaching well for its citizens, the congregation will will experience increased knowledge of God's word and experience changes in life, especially growth in spirituality. In this paper, the author presents the Contextual Learning model for discussion at the next stage. The learning model is a learning model in formal schools but it is very strategic to be applied in building church members. One form of the learning process of this model can use facilities that directly involve the congregation itself and also facilities around the congregation including other fellow congregations, therefore by using the facilities and infrastructure that are around it, coaching can be more easily carried out effectively. and easier to understand, especially to be practiced by church members or the congregation it self.